The Effectiveness Of Acupressur And Rebozzo Techniques In Preparation For Delivery In Mandiri Midwife Practices, Gowa Regency - Sri Wahyuni Bahrum; Irma Sri Rejeki; Fadlyatul Fajri (CV. Inara, 2023)
Uterine contractions play a very important role in the smooth delivery process. However, some mothers experience problems in uterine contractions which will result in the length of the labor process. So in some cases need induction assistance. Advances in medical science in terms of acupressure and rebozzo have become several solutions for certain treatments without involving chemistry in it. This study aims to be applied directly to mothers in labor in this case to help reduce contraction pain during the labor process. This study used the independent t-test of Mann Whitney which was previously tested for normality. The test results showed that acupressure and rebozzo were effective in reducing labor pain in mothers who were facing labor at the Independent Midwife Practices in Gowa district, as seen from the results of the independent t-test, which was obtained p-value = 0.000 (0.05). This study is useful for mothers to reduce labor pain by means of acupressure and rebozzo therapy.